(untitled) (Journal of Governance and Development (JGD), 2016)
Information is power is an effective quote in the public space, as the level of information and awareness of the society determine the degree of influence they exercise. This study investigates the effect of economic, financial-market, institutional and social factors on corporate carbon disclosure. This study determines the influence social factors have on corporate voluntary carbon disclosure in the real estate sector of Malaysia. Data was collected from 2013 annual reports of 126 listed companies in the real estate sector, comprising sixteen (16) property investment companies, seventy-six (76) property companies and thirty-four (34) construction companies in Malaysia. The analysis was conducted with Partial Least Square-Structural Equation Modeling, and bootstrapping. The result shows that social factor has a significant influence in determining voluntary carbon disclosure, among other factors. The constructs that have the strongest influence on voluntary carbon disclosure are firm size and political visibility. The implication is that the size and visibility of a company is significantly increases social pressure on a company hence it voluntarily participates in carbon disclosure.